2023
DOI: 10.3389/fnut.2023.1145068
|View full text |Cite
|
Sign up to set email alerts
|

Fish waste to sustainable additives: Fish protein hydrolysates alleviate intestinal dysbiosis and muscle atrophy induced by poultry by-product meal in Lates calcarifer juvenile

Abstract: Valorising waste from the processing of fishery and aquaculture products into functional additives, and subsequent use in aquafeed as supplements could be a novel approach to promoting sustainability in the aquaculture industry. The present study supplemented 10% of various fish protein hydrolysates (FPHs), obtained from the hydrolysis of kingfish (KH), carp (CH) and tuna (TH) waste, with 90% of poultry by-product meal (PBM) protein to replace fishmeal (FM) completely from the barramundi diet. At the end of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 77 publications
0
3
0
Order By: Relevance
“…A study with similar size barramundi (starting at 2.5 g) where FM was progressively replaced by varying proportions of alternative protein ingredients, including lupin kernel, black soldier fly meal and poultry by-product meal, also found a correlation between higher rates of FM substitution with the proliferation of opportunistic pathogens in the genus Aeromonas and Vibrio (Gupta et al, 2020). Similarly, an increase in Photobacteria, another opportunistic pathogen, was described for juvenile barramundi (starting at 7.25 g) fed poultry-by product meal, but functional feeds (e.g., fish protein hydrolysates) were able to alleviate intestinal dysbiosis (Chaklader et al, 2023).…”
Section: Discussionmentioning
confidence: 79%
“…A study with similar size barramundi (starting at 2.5 g) where FM was progressively replaced by varying proportions of alternative protein ingredients, including lupin kernel, black soldier fly meal and poultry by-product meal, also found a correlation between higher rates of FM substitution with the proliferation of opportunistic pathogens in the genus Aeromonas and Vibrio (Gupta et al, 2020). Similarly, an increase in Photobacteria, another opportunistic pathogen, was described for juvenile barramundi (starting at 7.25 g) fed poultry-by product meal, but functional feeds (e.g., fish protein hydrolysates) were able to alleviate intestinal dysbiosis (Chaklader et al, 2023).…”
Section: Discussionmentioning
confidence: 79%
“…Fish protein hydrolysates restore gut microbial composition in farmed juvenile seabass fish, indicating improvements on aquafeed formulations. The anti-inflammatory effect imparted by fish proteins is noteworthy [141]. The anti-inflammatory feature gives a competitive marketing edge to fish protein hydrolysates over poultry hydrolysates.…”
Section: Other Fish Proteins and Derivativesmentioning
confidence: 99%
“…Compositional considerations such as proximate, amino acid and fatty acid composition and the presence of anti-nutritional compounds have been paramount. Studies have also reported on the health and immune status of the fed fish (such as histological, blood biochemistry and gut microbiome results; Chaklader et al 2021a;Jannathulla et al 2021;Alfiko et al 2022;Aragão et al 2022;Chaklader et al 2023a). Of equal importance is the consideration of operational/ supply parameters for the inclusion of novel ingredients, such as their consistency of quality, cost, transport logistics and scale of production or supply (Hua et al 2019).…”
Section: Alternate Aquafeed Ingredients: Food and Consumer Science As...mentioning
confidence: 99%